Representation of corruption in popular culture: the cases of the Siqlla, K'anchisand "Doctorcitos" dances - Murguía Sánchez, Luis Ernesto (2021)
The study aims to present the phenomenon of corruption based on social criticism in popular culture. The results constitute the ethnographic description of the dance “los doctores” Siqlla that is danced in Cusco, “Doctorcitos” in the Peruvian-Bolivian altiplano and the “Docturcha” among the K’anchis of the district of Ayaviri, department of Puno; followed by an ethno-classification of “doctors”, “doctorcitos” and “doctorazos”, with real of false title from the university’s main quarry. The conclusions constitute a generalization for particular cases and point out that corruption is seen as degradation, decomposition or deviation from virtue, which is why they are the object of social criticism based on popular representation, dance and, within it, the resource of mockery, joking and derision is privileged.